Ilu ludzi na świecie mówi po polsku? - Bogdan Walczak (Język. Religia. Tożsamość, 2019)
The author, referring to data from over ten years ago (owing to a lack of more recent data), presents the Polish language as – contrary to a common stereotype – one of the most largely spoken languages in the world. On the list of the world’s largest languages in descending order, Polish is ranked at the end of the top twenty, or, more likely, just outside the top twenty (Alfred F. Majewicz convincingly argues that a more accurate placing of Polish is impossible).